Generalized criteria for blind multivariate signal equalization. - Thirion-Moreau, N.
We consider the problem of blind multivariate signal equalization. Assuming that the input signals are i.i.d. and statistically mutually independent, we propose both a generalization of some available equalization criteria and a generalization of some source separation criteria to the convolutive case. Hence, we obtain a new generalized class of objective function for blind equalization
Keywords: MIMO equalization; Blind multivariate signal equalization; Convolution; Cross-cumulants.; Generalized criteria; Generalized objective function; i.i.d. input signals; Multi-input multi-output equalization; Statistically mutually independent input signals